2013
DOI: 10.1089/ten.tea.2011.0653
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of Endothelial Cells and Endothelial Progenitor Cells on Peptide-Linked Polymers in Shear Flow

Abstract: The initial adhesion of human umbilical vein endothelial cells (HUVECs), cord blood endothelial colony-forming cells (ECFCs), and human blood outgrowth endothelial cells (HBOECs) was studied under radial flow conditions. The surface of a variable shear-rate device was either coated with polymer films or covered by synthetic fibers. Spin-coating was applied to produce smooth polymer films, while fibrous scaffolds were generated by electrospinning. The polymer was composed of hexyl methacrylate, methyl methacryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…One approach to promote rapid endothelialization of “off‐the‐shelf” vascular prostheses involves utilizing bioactive luminal coatings to support EOC adhesion, proliferation, and differentiation . As previously noted, PEG‐Scl2‐2 hydrogels have been shown to maintain the resistance to the platelet adhesion and activation characteristic of pure PEG hydrogels and the resistance to platelet aggregation and activation associated with pure Scl2‐2 proteins .…”
Section: Discussionmentioning
confidence: 99%
“…One approach to promote rapid endothelialization of “off‐the‐shelf” vascular prostheses involves utilizing bioactive luminal coatings to support EOC adhesion, proliferation, and differentiation . As previously noted, PEG‐Scl2‐2 hydrogels have been shown to maintain the resistance to the platelet adhesion and activation characteristic of pure PEG hydrogels and the resistance to platelet aggregation and activation associated with pure Scl2‐2 proteins .…”
Section: Discussionmentioning
confidence: 99%
“…Second, it has been shown that a low flow rate supports better cell adhesion on graft surfaces during in vitro culture. 34 Prolonged adhesion is crucial to cell proliferation and eventual endothelialization of a TEVG.…”
Section: Discussionmentioning
confidence: 99%
“…These include modifications such as heparin-coated scaffolds, VEGF, antibodies, and various peptides. 28,34,38,46 Such modifications may improve initial cell seeding, which, in turn, may expedite in vitro endothelialization and tissue formation on bioreactor-cultured TEVGs. In addition, there is still some controversy on the role of EPCs and the role of specific subsets of these cells.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of the adsorbed protein layer can act to hide the ligands of interest from view of the adhering cells . Therefore, the peptides are often immobilized to a non‐fouling interface [usually poly(ethylene glycol)] that resist non‐specific adsorption of proteins yet enable adhesion of cells that possess the appropriate integrin receptors . Additionally, the generation of synthetic materials that bare cell‐adhesive peptides on the surface provide a researcher with control over the surface density of the ligand, and this jurisdiction over surface density enables a researcher to regulate various aspects of adherent cell behaviour including adhesion, proliferation, migration, etc .…”
Section: Polymeric Biomaterials That Promote Endothelializationmentioning
confidence: 99%